2021
DOI: 10.3390/v13071369
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake and Intracellular Phosphorylation of GS-441524: Implications for Its Effectiveness against COVID-19

Abstract: GS-441524 is an adenosine analog and the parent nucleoside of the prodrug remdesivir, which has received emergency approval for treatment of COVID-19. Recently, GS-441524 has been proposed to be effective in the treatment of COVID-19, perhaps even being superior to remdesivir for treatment of this disease. Evaluation of the clinical effectiveness of GS-441524 requires understanding of its uptake and intracellular conversion to GS-441524 triphosphate, the active antiviral substance. We here discuss the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 80 publications
(107 reference statements)
0
12
0
Order By: Relevance
“…Previously, we suggested that endogenous https://www.guidetopharmacology.org/GRAC/LigandDisplayForward?ligandId=2844 competes with GS‐441524 for cellular uptake by nucleoside transporters such as equilibrative nucleoside transporter 1, and the perceived rate‐limiting first step of its phosphorylation to GS‐441524 monophosphate eventually leading to the formation of GS‐441524 triphosphate 11 . Under physiological conditions, extracellular and intracellular adenosine levels are in the submicromolar range, but these levels are significantly elevated in hypoxia and critical illness, occasionally being increased by 5‐ to 10‐fold or more, e.g.…”
Section: Effects Of Extracellular and Intracellular Adenosine Levels ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we suggested that endogenous https://www.guidetopharmacology.org/GRAC/LigandDisplayForward?ligandId=2844 competes with GS‐441524 for cellular uptake by nucleoside transporters such as equilibrative nucleoside transporter 1, and the perceived rate‐limiting first step of its phosphorylation to GS‐441524 monophosphate eventually leading to the formation of GS‐441524 triphosphate 11 . Under physiological conditions, extracellular and intracellular adenosine levels are in the submicromolar range, but these levels are significantly elevated in hypoxia and critical illness, occasionally being increased by 5‐ to 10‐fold or more, e.g.…”
Section: Effects Of Extracellular and Intracellular Adenosine Levels ...mentioning
confidence: 99%
“…Since GS‐441524 is a nucleoside analog lacking the McGuigan moiety characteristic of ProTides, its pharmacokinetics (PK) differs markedly from that of remdesivir. Notably, cellular uptake of GS‐441524 is believed to be dependent upon membrane‐bound transporters since it is hydrophilic with limited ability to cross cell membranes by diffusion 11 . By contrast, uptake of remdesivir appears to be mediated by diffusion, which is facilitated by its hydrophobic prodrug moieties, thus probably to a large extent being independent of membrane‐bound transporters 5,6,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GS-441524 is reported to be an effective treatment of feline infectious peritonitis (FIP) caused by feline coronavirus ( Dickinson et al, 2020 ). The cellular uptake and phosphorylation of GS-441524 ( Rasmussen et al, 2021 ), PK of ester prodrugs of GS-441524 in mice ( Wei et al, 2021 ), and the in vivo efficacy in a SARS-CoV-2 mouse model ( Li et al, 2021 ) of GS-441524 have been reported recently. In addition, PK and efficacy of a triester prodrug of GS-441524 in mouse and ferret models of SARS-CoV-2 infection have been reported ( Cox et al, 2021 ; Schafer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…GS-441524 is reported to be an effective treatment of feline infectious peritonitis (FIP) caused by feline coronavirus [10]. The cellular uptake and phosphorylation of GS-441524 [11], PK of ester prodrugs of GS-441524 in mice [12], and the in vivo efficacy in a SARS-CoV-2 mouse model [13] of GS-441524 have been reported recently. In addition, PK and efficacy of a triester prodrug of GS-441524 in mouse and ferret models of SARS-CoV-2 infection have been reported [14, 15].…”
Section: Introductionmentioning
confidence: 99%